Risk of hospital-acquired legionellosis from microbial contamination of potable water at a bone marrow transplantunit in a Czech university hospital - Holy, O.; Matouskova, I.; Juraskova, E. (Химия и технология воды, 2014)
The investigated of the potable water treatment room and the sanitary facilities of patient boxes was held. The potable water treatment room had three collection points (ball valves), while in the sanitary facilities potable water was collected from the tap, shower, and the flush tank. A swab was taken from the inside wall of the toilet tank. The samples and swabs of the flush tank water were Legionella pneumophila sg 1 and sg 6A positive. Disinfection of flush tanks with chlorine agents was recommended.